2020
DOI: 10.3390/plants9080982
|View full text |Cite
|
Sign up to set email alerts
|

The Seedlings of Different Japonica Rice Varieties Exhibit Differ Physiological Properties to Modulate Plant Survival Rates under Submergence Stress

Abstract: Oryza sativa is a major food crop in Asia. In recent years, typhoons and sudden downpours have caused field flooding, which has resulted in serious harm to the production of rice. In this study, our data revealed that the plant heights of the five Japonica varieties increased during submergence. The elongation rates of TN14, KH139, and TK9 increased significantly during submergence. Chlorophyll contents of the five varieties significantly decreased after submergence and increased after recovery. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The accumulation of ROS scavenging enzymes has been determined to be one of the most important responses during LT stress [60]. Moderate flooding could further enhance the antioxidant capacity of plants, inhibit membrane peroxidation and reduce the aggravation of leaf peroxidation damage [61]. Our study found that under LT Fig.…”
Section: Effect Of Flooding On the Antioxidant System Under Lowtemper...mentioning
confidence: 52%
“…The accumulation of ROS scavenging enzymes has been determined to be one of the most important responses during LT stress [60]. Moderate flooding could further enhance the antioxidant capacity of plants, inhibit membrane peroxidation and reduce the aggravation of leaf peroxidation damage [61]. Our study found that under LT Fig.…”
Section: Effect Of Flooding On the Antioxidant System Under Lowtemper...mentioning
confidence: 52%
“…Thus, ‘regulation of hydrogen peroxide metabolic process’ and ‘systemic acquired resistance, salicylic acid mediated signaling pathway’ are evidenced to be linked to flooding-tolerant responses in soybean. Besides, rice was also evidenced to be involved with these two pathways under flooding stress 69 , 70 . In soybean roots, cell wall and aerenchyma will swell under flooding.…”
Section: Discussionmentioning
confidence: 99%
“…Plant waterlogging resistance is controlled by a combination of multiple factors [ 50 , 51 , 52 , 53 , 54 ]. The specific adaptive mechanism involves secondary signal transduction, gene expression, and protein synthesis, antioxidant enzyme system, and fermentation pathway under hypoxia stress [ 55 , 56 , 57 , 58 ].…”
Section: The Role Of H 2 S In Response To Hypoxia Stress Induced By Waterlogging In Plantsmentioning
confidence: 99%